Joint forest Management at Village Level: a Cognitive Analysis - Rishi, Parul (Indian Forester, 2002)
Effective local control with Forest Department requires a willingness and ability of government to empower the peoples' local institutions and this empowerment is possible only when the people are aware of different roles and processes of JFM. In this regard , the cognitive analysis of JFM had been planned to study the level of knowledge and awareness of people towards JFM through JFM Awareness Index (JAI). The results indicate a limited amount of cognitive level assimilation of JFM. This limited level of awareness and knowledge at cognitive level acts as a constraint in the institutionalisation of JFM. Thus , sustained awareness generating efforts are required at micro-level through village workshops , study tours , exposure visits , edUcational campaigns etc. to raise the level of knowledge and awareness of people towards the broader objective of institutionalisation and sustenance of JFM programme.